INNOVATIVE TECHNOLOGIES IN PHYSICAL EDUCATION OF STUDENTS AT TECHNICAL UNIVERSITIES (World Bulletin of Physical Education and Sports Science, 2025)
This article examines the specific features of applying innovative technologies in the process of physical education of students at technical universities. The aim of the study was to determine the effectiveness of modern methods and digital learning tools in organizing the educational and training process. The research involved 25 students of group 57-YXTE-24 from Namangan State Technical University. During the eight-week experiment, innovative forms of training were implemented, including elements of interval, circuit, and game-based training, as well as digital monitoring of students’ physical development indicators. The results of the experiment demonstrated that the use of innovative approaches contributes to increasing students’ motivation and improving indicators of strength, endurance, speed, and flexibility. The practical significance of the research lies in the possibility of introducing the proposed methods into the system of physical education at technical universities.
Keywords: Physical education, innovative technologies, students, technical university, physical qualities, pedagogical experiment, digital methods.Physical education, innovative technologies, students, technical university, physical qualities, pedagogical experiment, digital methods.